ChemInform Abstract: Synthesis of Anhydrous K2TiOF4 via a Mild Hydrothermal Method. Issue 49 (December 2015) - Felder, Justin B.; Yeon, Jeongho; zur Loye, Hans‐Conrad
Abstract: Single crystals of K2 TiOF4 are grown hydrothermally from mixtures of TiF3, KF, HF, and H2 O (autoclave, 200 °C, 24 h, 75% yield).